How Is Collective Identity Possible in Democracies? Political Integration and the Leitkultur Debate in Germany - Simon Bein (Politische Vierteljahresschrift, 2022)
The quest for a~common collective identity has become a~challenge for modern democracy: Liberal demands for greater inclusion and individual freedom, aspirations for a~strong and solidaric political community, as well as nationalist or right-wing populist calls for exclusion and a~preservation of hegemonic national identities are creating tensions that cannot be overlooked. This article therefore formulates the central question of how collective identity can be possible in a~liberal democracy. Based on a~case study on Germany, it will therefore be examined whether Leitkultur as a~model of political integration can serve in generating a~functional democratic collective identity. The necessary benchmarks guiding the analysis will be defined beforehand from a~systems-theoretical perspective, balancing inclusion and exclusion within three crucial dimensions: normative basics, historic continuity, and affirmative bindings. The results show that a~static definition of a~German Leitkultur would in the long run neither achieve functional inclusion nor be able to generate the necessary cohesion of a~political community, especially regarding the second and third identity dimensions.
Keywords: 320; Integration; Political Culture; Identity Politics; Citizenship; Systems Theory; Integration; Politische Kultur; Identitätspolitik; Citizenship; Systemtheorie